The elastic system: A review of elastin-related techniques and hematoxylin-eosin/phloxine applicability for normal and pathological tissue description - Ruiz, Thalles Fernando Rocha [UNESP]; Ferrato, Luara Jesus [UNESP]; de Souza, Lorena Gabriela [UNESP]; Brito-Filho, Gervásio Evangelista [UNESP]; Leonel, Ellen Cristina Rivas; Taboga, Sebastião Roberto [UNESP] (Elsevier, 2024)
The elastic system is one of the most developed interstitial elements in connective tissue. With diverse functions, pre-elastic and elastic fibers contribute to the distensibility and malleability of several organs. Also, microanalyses of the elastic system were obtained by different histological techniques that were employed over years to describe normal and pathological conditions. Compared to conventional stains, hematoxylin-eosin/phloxine (HE/P) under fluorescence and confocal microscopy presented a highly detailed observation of the elastic system in different organs and scenarios. This technique provides a better demarcation of the elastic fibers, favoring their description in relation to their deposition and aggregation in different organs. Also, fibrils with low aggregation or loss of this characteristic are observed in an optimal view in the skin, heart valves, and large-caliber blood vessels. Degradation, fragmentation, and rupture were also well described by the HE/P technique. Several organs, such as the mammary gland, prostate, skin, aorta, and lung, could be described with precision under this technique. In association with non-linear microscopy, the results of the research presented in this paper improved and detailed characteristics of precise pathogenesis. Thus, the HE/P technique presented an interesting efficiency to demonstrate alterations and structures in which the elastic system showed a relevant role, and when compared to other techniques it demonstrated a similar or better result. In addition, it is expected that future studies can reveal more information about the elastin and interactions with specific dyes, thus allowing a greater understanding of the great efficiency of this technique.
Keywords: Connective tissue; Elastin; Histotechnology